Studi teknis dan kelayakan usaha kapal Pole and Line: Technical Studies and Business Feasibility of Pole and Line Vessels - David Yusak Gandaria; Frangky Ernes Kaparang; Mariana Elizabeth Kayadoe; Kawilarang Warouw Alex Masengi; Lucia Manu; Fransisco Philep Theodorus Pangalila (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
The purpose of this study is to understand the technical aspects of fishing using the pole and line method, as well as to analyze the feasibility of the pole and line fishery. The research method used in this study is descriptive with a quantitative approach, conducted at PT Sari Usaha Mandiri, specifically on KM Sari Usaha 09, with a vessel specification of 25.73 m in length, 5.16 m in width, and 2.60 m in height. The components of the pole and line gear are a rod, a fishing line, and a hook. The fishing operation also involves the use of fish aggregating devices, which requires compliance with sea safety, fishing regulations, and storage requirements. The fishing technique employed is known as "banting," with the main catches being skipjack tuna and yellowfin tuna. The fishing area is located in the WPPN-RI 715. Based on the feasibility analysis, it can be concluded that the pole and line fishery is viable for business because the net benefit cost ratio is > 1 (1.097), the production output (351,600 kg) and revenue (IDR 6,328,800,000) exceed the break-even point of production (77,650 kg) amounting to IDR 1,397,704,483. The margin of safety is IDR 4,931,095,517 or 78%, the net present value is > 0 (IDR 3,485,024,022), the internal rate of return is > 5% (86%), and the payback period is 2.3 years.